Simple Additive Weighting dalam Penyaluran Dana Bantuan Sekolah Dasar - Afifah Trista Ayunda; Sarjon Defit; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2021)
School grants are the distribution of education funds for elementary schools sourced from the Boss Performance (Bos Kinerja). Boss Performance or school operational assistance is allocated for schools that are considered to have good performance. The issues that often arise is the distribution of school aid funds that are not on target, this is due to the absence of a method for distributing these funds, which has affect on the performance of the school education unit. Decision support systems with Simple Additive Weighting (hereinafter reffered to as SAW) method are used to encourage the quality of education services for elementary schools which are considered to have good performance in educational units. Moreover, its facilitate in making and supporting decisions in the distribution of elementary school assistance funds. In the result of this study found the final result 100 percent accuracy therefore adoption of the Simple Additive Weighting method helps in making decisions that are right on target in distributing primary school grants.